A multiple case analysis of designated study areas in the residences of Filipino home schooled children - Pagulayan, Joanna Joy H.
This study sought to study interior design elements (furniture, acoustics, lighting, air quality, temperature, color and space layouts of study spaces of homeschooled children. Focused on how the layouts and interior design elements (furniture, acoustics, lighting, air quality, temperature, color) of designated study areas of five (5) Filipino homeschooling families were chosen as respondents of the study where relate to and reflect their needs, movement, and processes of its users. were analyzed. This study supposed that since the children and parents are the main users of the space, they directly influence the built environment around them. The five cases consisted of families with children ages 6-11 years old (grade school) who have designated study areas in their residences. Respondents were selected using non- probability sampling. Data were gathered within a span of two months, involving an initial survey, interviews, site measurements, on-site observations, and photo documentation. This multiple case study employed Grounded Theory approach which involved coding and thematic analysis. Results from these methods showed that although there exist no mandated requirements for study areas for homeschoolers, the selected cases revealed common spatial needs such as storage and desk space., among others . It was also revealed that the study areas of the five cases we are chosen and laid out depending on which room/space was available. The different interior design elements of these spaces showed similarities and differences among the five cases. From the results, the space was analyzed and common themes were derived. These themes suggested that homeschooling acts as homeschooling became a created culture adapted by the families. This culture served as the basis for the users spatial needs like storage and desk space. This, in turn influenced the users design decisions (choice of furniture, layout, color) and additionally, its flexibility was reflected in the interior elements of the designated areas.